A bounded consistency theorem for strong summabilities. (1989) - Chun, C. S.; Freedman, A. R.
Abstract : The study of R-type summability methods is continued in this paper by showing that two such methods are identical on the bounded portion of the strong summability field associated with the methods. It is shown that this "bounded consistency" applies for many non-matrix methods as well as for regular matrix methods.